Teungku Dayah dan Kekuasaan Panoptik - Nirzalin Nirzalin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Abstract: This study examines the teungku dayah and panoptic power. It explores two main questions that firstly what serves as the basic for the Acehnese society obedience towards the teungku dayah? What power model that the tengku dayah apply so the people total obedience is honestly expressed whether in front and behind them. Theoretically, this study refers to power relation and hermeneutic theory that are introduced by Michel Foucault. The data of this study are collected through observation, in-depth interview and text studies. By closely study some dayahs (traditional Islamic boarding school) in north Aceh district, this study finds that teungku dayah could be determinant figure in Acehnese society. It is because not only they are religiously knowledgeable persons that are justified by religious norms, it is also influenced by three other resources: sacred (keuramat), blessed (beureukat) and accursed (temeureuka). As the sacred figure, Acehnese believe that teungku dayah could mediate God’s blessings to them. Against or defy to them could cause accurses. The belief of being accursed if one is defiant toward the Tengku, grants the total obedience toward the Tengku. These three concepts are crafted in people minds, hearts, and emotion so as if they are always being watched by the teungku any time and any place. Perhaps Cross Circuit Television (CCTV) best represents this condition in latest surveillance technology. Thus, these sources grant teungku dayah the panoptical power that is nonviolent, persuasive, absent, remote, total and comprehensive.Abstrak: Studi ini mengkaji tentang teungku dayah dan kekuasaan panoptik. Pertanyaan utama yang dikupas adalah apa yang mendasari lahirnya kepatuhan total masyarakat Aceh terhadap teungku dayah dan model kekuasaan seperti apa yang dimiliki oleh teungku dayah sehingga kepatuhan masyarakat terhadap mereka tidak hanya berlaku di depan tetapi juga di belakang. Proses kajian dilakukan dengan menggunakan perspektif teoritik kekuasaan Michele Faucault dan metode hermenutik. Maka pelbagai data yang digali melalui observasi, wawancara mendalam dan studi dokumen diperlakukan sebagai teks sosial. Lalu, pelbagai data tersebut ditafsirkan melalui teknik tafsir lingkaran hermeneutik. Penelitian yang dilakukan di beberapa dayah di Aceh Utara ini menemukan bahwa kekuasaan teungku dayah terhadap masyarakat Aceh selain didasari oleh penguasaan ilmu agama dan justifikasi normatifitas agama juga dipengaruhi oleh 3 (tiga) sumberdaya lainnya yaitu keuramat (karamah), beureukat(barakah) dan temeureuka (kualat).. Maka kekuasaan teungku dayah terhadap masyarakat Aceh bersifat panoptik yaitu tanpa kekerasan fisik, tanpa paksaan, tanpa kehadiran, jarak jauh, total dan menyeluruh.